Comparison Between Robotic Finger Therapy Exercise and Conventional Exercise on the Range of Motion of the Metacarpophalangeal Joints: Study of Post-stroke Patients at Diponegoro National Hospital - Daniel Andry Kurniawan; Sri Wahyudati; Tanti Ajoe Kesoema; Hari Peni Julianti; Rahmi Isma Asmara Putri; Erna Setiawati; Dewi Kusuma Hartono (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND : Metacarpophalangeal (MCP) joints range of motion (RoM) exercise can be done using either conventional exercise or robotic finger therapy. This study aimed to compare MCP joints RoM improvement between conventional exercise and robotic finger therapy exercise in post-stroke patients. METHOD : This study was a randomized controlled trial pre and post test controlled group design. The data were taken from individuals aged 45-65 years with a history of stroke undergoing medical rehabilitation at the Diponegoro National Hospital before and after intervention (robotic finger therapy exercise vs conventional exercise) for 6 weeks. MCP joints RoM was measured using goniometer before and after the intervention. Datas were analysed using SPSS ver 20.0. Normality of data distribution would be assessed using the Shapiro-Wilk test. Differences in the RoM of MCP joints before and after treatment in each group were tested using paired t-test. Group differences were tested using unpaired t-test. RESULT :  There was significant RoM improvement in each MCP joint in each group before and after the treatment (p<0.05). There was no significant difference in RoM improvement between groups (p>0.05). CONCLUSION : Both robotic and conventional therapy significantly improve MCP joints RoM in post-stroke patients. There was no significant difference in MCP joints RoM improvements between robotic finger therapy and conventional exercise.